SPECIFIC FEATURES OF THE USE OF DIGITAL TECHNOLOGIES IN THE DEVELOPMENT OF INDUSTRIAL ENTERPRISES - Donayeva Feruza Burxon qizi (Ecominds Press, 2025)
The article examines the concept of digitalization and its role in economic development. It highlights the essence of the digital transformation process, the strategy for implementing this process in the activities of enterprises and ways to implement this strategy, the grouping of digital technologies, the advantages and possible harm of implementing these technologies, the stages and models of implementing a digital enterprise, and provides practical recommendations.
Keywords: Digitalization, digital enterprise, digital transformation, cloud technology, big data, digital transformation models, process model, network model, technology model, matrix model.